Anthrax meningoencephalitis complicated with brain abscess — A case report. (July 2021) - Popescu, Corneliu Petru; Zaharia, Mihaela; Nica, Maria; Stanciu, Delia; Moroti, Ruxandra; Benea, Serban; Melinte, Violeta; Vasile, Teodor; Ceausu, Emanoil; Ruta, Simona; Florescu, Simin Aysel
Highlights: The patient was a 42-year-old male shepherd. Anthrax meningoencephalitis with brain abscess was successfully treated. Polymerase chain reaction: Bacillus anthracis cerebrospinal fluid, cutaneous lesions. Magnetic resonance imaging: meningeal enhancement, multiple intraparenchymal lesions. Magnetic resonance imaging at day 22 showed left parietal lobe lesion compatible with abscess. Abstract: Bacillus anthracis is a sporulating gram-positive rod whose main route of entry into the human body is cutaneous. Anthrax meningitis is usually fulminant and fatal. We present here a successfully treated case of anthrax meningoencephalitis complicated with brain abscess. The patient was a shepherd, with disease onset 7 days prior to hospital admission with fever, chills, occipital headache, and vertigo, followed by right hemiplegia, motor aphasia, agitation and coma. He had cutaneous lesions with black eschar on the limbs, which was a clue (along with his occupation), for diagnosis suspicion. The polymerase chain reaction for B. anthracis DNA was positive in both cerebrospinal fluid and cutaneous lesions. The cerebrospinal fluid was compatible with bacterial meningitis without being haemorrhagic. Magnetic resonance imaging showed meningeal enhancement and multiple intraparenchymal heterogeneous lesions with an important haemorrhagic component in the left parietal lobe, surrounded by vasogenic oedema with maintenance, 22 days later, of the left parietal lobe lesion, having a ring contrast enhancement and a central diffusion restriction, compatible with an abscess. From admission, he was intensively treated with combined large-spectrum antibiotics; this could be the most valuable factor in the successful outcome.